Limited joint mobility in diabetes mellitus. Issue 2 (February 1985) - Campbell, R R; Hawkins, S J; Maddison, P J; Reckless, J P
Abstract : The relationship of limited joint mobility and finger joint contractures in diabetics to age of onset, duration, and control of diabetes has not been established. We measured the mobility of metacarpophalangeal, wrist, elbow, and ankle joints and assessed the prevalence of finger joint contractures in 254 young diabetics and 110 controls. The presence of microvascular disease was assessed by ophthalmoscopy and urine analysis for proteinuria. An estimate of long-term diabetic control was obtained from a postal questionnaire. A generalised reduction in joint mobility was present in diabetics of all ages two years after diagnosis. The reduction in joint mobility in controls between the ages of 12 and 13 was exaggerated in the diabetics. Diabetics diagnosed before puberty were more severely affected than those with a postpubertal onset, independent of duration of diabetes. Finger joint contractures were a significant feature of longstanding diabetics (nine years or more duration) only.